Matthew - The Movie Matthew Bourne's The Car Man, a DVD review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2002)
DVD Review. PALABRAS CLAVE: Matthew Bourne, The Car Man.
Carmen. Warner Vision International.